Pombagira: a imagem dos desejos inconfessos projetados em um feminino indesejado - Araújo, Paloma Gisele Muniz (2023)
The general objective of this dissertation was to investigate, from the perspective of Carl Gustav Jung's depth psychology, aspects of the collective shadow that are projected onto the image of the Pombagira and its symbols in Brazilian culture. Therefore, a symbolic reading of this myth was also necessary, in order to reflect on the construction of sexist and racist stereotypes in Brazil. To achieve this objective, we conducted a literature review, aiming at contributing to expand the knowledge in the sphere of mythological studies in the field of Jungian and archetypal psychology. By adopting a multisciplinary perspective, we propose that the understanding of Brazilian soul requires considering decolonial thinking as well as historical, social and anthropological processes. Pombagira is known as a Brazilian deity originating from the clash of different worldviews as a consequence of the African diaspora. Currently worshiped in African-based religions in Brazil, and sought after for responding to appeals related to affection, love and sexuality, she is considered, perhaps, the most intriguing and contradictory deity, above all, for everything that it refuses to be. It ensures access to the paths of the world of instincts, sexual impulses and unconfessed desires. She is popularly known as the queen of crossroads, as she is the guardian of all paths that lead to desire. She is also recognized for her rebelliousness and desire for freedom, not accepting the restriction of her desire by male domination. At the same time, she claims the place of protagonist in her story. However, she is culturally demonized and reduced to racist and sexist stereotypes, as she is related to African-based religions and has the psychological characteristics of a woman who opposes patriarchal social conventions. Studying an originally Brazilian myth allows access to a despised fragment of the Brazilian soul, providing subsidies for a better understanding of the ancestry of millions of Afro-descendants